2018
DOI: 10.2147/cmar.s158335
|View full text |Cite
|
Sign up to set email alerts
|

Emergency treatment of complicated colorectal cancer

Abstract: AimTo find evidence to suggest the best approach in patients admitted as an emergency for complicated colorectal cancer.MethodsThe medical records of 131 patients admitted as an emergency with an obstructing, perforated, or bleeding colorectal cancer to Noble’s Hospital, Isle of Man, and the Umberto I University Hospital, Rome, were retrospectively evaluated. Patients were divided in 3 groups on the basis of the emergency treatment they received, namely 1) immediate resection, 2) damage control procedure and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…Similar to our data, the practice of serial interventions has been shown to be a protective factor in other studies (15,(45)(46)(47). In contrast, other authors concluded that resections with anastomosis ensure better survival, including for occlusive tumors (48).…”
Section: Discussionsupporting
confidence: 90%
“…Similar to our data, the practice of serial interventions has been shown to be a protective factor in other studies (15,(45)(46)(47). In contrast, other authors concluded that resections with anastomosis ensure better survival, including for occlusive tumors (48).…”
Section: Discussionsupporting
confidence: 90%
“…Perforated CRC patients face the life-threatening conditions of both malignant disease and sepsis (1). These patients often require emergent surgery (1), with perioperative mortality ranging between 11%-21% (13)(14)(15)(16)(17)(18). Furthermore, even after perforated CRC patients recover from peritonitis and the perioperative phase, colorectal perforation is reported to be a risk factor for poor prognosis (2-5) and high recurrence (3,6).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we aimed to investigate the role of high and low IMA ligation and no other confounding factors (i.e. radiation therapy, neoadjuvant chemotherapy and open surgery, benign lesions, emergency setting) (9,(31)(32)(33)(34)(35) in the impairment of the defecatory, sexual and urinary function after TME. The ligation of the IMA at its origin may accidentally damage the superior hypogastric plexus, which is interconnected with the inferior hypogastric plexus.…”
Section: Discussionmentioning
confidence: 99%